Social policy : an introduction - Blakemore, Kenneth, 1948- (Buckingham ; Phildelphia : Open University Press, 2003)
"Social Policy: An Introduction is essential reading for students beginning or building on their study of social policy or welfare. It can be used in undergraduate degree courses, postgraduate diplomas and Masters level and pre-degree studies. The book is an invaluable reference resource for practitioners, professionals of policy makers in fields including health, medicine and nursing, housing, social services and counselling, education, law and criminology."--BOOK JACKET.
1. The Subject of Social Policy -- 2. Ideas and Concepts in Social Policy -- 3. The Development of Social Policy in Britain -- 4. Who Gets What? Slicing the Welfare Cake -- 5. Social Policy, Politics and Social Control -- 6. Who Makes Policy? The Example of Education -- 7. Work and Welfare -- 8. Are Professionals Good for You? The Example of Health Policy and Health Professionals -- 9. Utopias and Ideals: Housing Policy and the Environment -- 10. Community and Social Care -- 11. Devolution and Social Policy -- 12. Conclusion: The Future of Social Policy.
Includes bibliographical references (p. [276]-284) and index.
Newaz
Keywords: Social policy; Great Britain -- Social policy